Environmental Legal Liability for Radioactive Contamination in Exported Frozen Shrimp Products in the Cikande Industrial Area - Ardy Bryan Ompusunggu; Christin Septina Basani (Golden Ratio of Law and Social Policy Review, 2026)
The detection of radioactive Cesium-137 (Cs-137) contamination in Indonesian exported frozen shrimp products in 2025 raised concerns over environmental protection, food safety, consumer protection, and international trade sustainability. This study analyzes environmental legal liability for radioactive contamination in the fishery industry supply chain in the Cikande Industrial Area and examines legal protection for consumers, workers, surrounding communities, and affected business actors. This study uses normative legal research with statutory, conceptual, and case approaches. The legal materials include regulations on environmental protection, consumer protection, nuclear energy, radiation safety, and food safety. The findings show that Cs-137 contamination indicates weak implementation of the precautionary principle, inadequate supervision of radioactive hazardous waste, and limited cross-agency coordination. Legal liability should be constructed through strict liability and the polluter pays principle, requiring the polluting party to bear restoration, compensation, and victim recovery costs. This study recommends strengthening radioactivity supervision, improving inter-agency coordination, and establishing risk-based preventive monitoring to ensure food safety, environmental protection, and sustainable fishery exports.